Usage of Two Probes Method for Modelling of Nano Structure Charge Transport: Comparative Study of Charge Transport in Traditional and Nano-based Devices (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Implementation of modeling of charge transport in Neno structure using two probes method has been proposed. Nanotechnology is manipulation of matter on an atomic, molecular and supra molecular scale. Earliest, widespread description of Nanotechnology referred to particular technological goal of precisely manipulating atoms and molecules for fabrication of macro scale products. Now it has been referred to as molecular Nanotechnology. In this research MATLAB has been used to make comparative study of traditional and Nano based devices performance considering several factors such as Cost, Power consumption, portability, quality factor, mass production, Environment friendly. The factor such as energy consumption, energy efficiency delayed efficiency are alos considered here. Molecular Nanotechnology has been termed as technology that is dependent on ability to develop structures to complex, atomic specifications. This technology is based on concept of Nano arrangements of machines to explore new components from existing ones. It doesn’t works on randomization of molecules but on systematic positioning of every single molecule. The research would withdraw conclusion and discuss the scope of research according to results and discussion.